2020
DOI: 10.3389/fpsyt.2020.00875
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Three Simplified Chinese Online-Related Addictive Behavior Instruments Among Mainland Chinese Primary School Students

Abstract: Background/Objective: There are inadequate screening instruments for assessing specific internet-related addictions among mainland Chinese primary school students. Therefore, the present study validated the psychometric properties of three simplified Chinese online-related addictive behavior instruments among mainland Chinese primary school students. Method: Fourth to sixth graders (n = 1108; 48.3% males; mean [SD] age = 10.37 years [0.95]) completed the nine-item Internet Gaming Disorder Scales-Short Form (IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 57 publications
13
77
0
Order By: Relevance
“…Hence, as frontline healthcare workers' fear of COVID-19 increases, their anxiety levels may also increase. These findings are supported by previous COVID-19 studies among other populations ( 4 6 , 49 ). This may suggest that COVID-19 is significantly related to other psychological problems (e.g., hypochondriasis, internet, or social media addiction) that were not included in this study ( 50 ).…”
Section: Discussionsupporting
confidence: 90%
“…Hence, as frontline healthcare workers' fear of COVID-19 increases, their anxiety levels may also increase. These findings are supported by previous COVID-19 studies among other populations ( 4 6 , 49 ). This may suggest that COVID-19 is significantly related to other psychological problems (e.g., hypochondriasis, internet, or social media addiction) that were not included in this study ( 50 ).…”
Section: Discussionsupporting
confidence: 90%
“…[26][27][28][29] Although the original BSMAS asks participants to consider problematic behaviors over the past year, the present study revised the timeframe to ''past week.'' Moreover, the Chinese BSMAS used in the present study was validated by Yam et al 8 and Chen et al 20 The internal consistency of the Chinese BSMAS in the present study was very good (a = 0.875).…”
Section: Participants and Proceduressupporting
confidence: 61%
“…Prior studies have demonstrated very good psychometric properties for the IGDS-SF9. 8,20,21 Although the original IGDS-SF9 asks participants to consider IGD symptoms over the past year, the present study revised the timeframe to ''past week.'' Moreover, the Chinese IGDS-SF9 used in the present study was validated by Yam et al 8 and Chen et al 20 The internal consistency of the Chinese IGDS-SF9 in the present study was excellent (a = 0.922).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…This brand-new model of teaching and learning means that a great deal of time is needed among teachers and students to learn run-in and debugging, so it is understandable that international students experienced difficulties adapting to this new mode, resulting in psychological distress. The main reason for such difficulties was poor adaptation to the new learning mode [ 24 , 62 ], and instead over-indulging on the internet [ 25 ], which can lead to offline communication obstacles.…”
Section: Discussionmentioning
confidence: 99%